The Optimization Of Shell And Tube Cycle Recuperator Design In Organic Rankine Geothermal Power Plant - Muhammad Rifqi Dwi Septian (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2023)
Indonesia has the largest geothermal potential in the world by saving 40 percent of the world's geothermal resources. Geothermal energy manifestations in Indonesia are no less than 252 locations spread across Sumatra, Java, Nusa Tenggara, Bali, Sulawesi to Maluku. Indonesia has a total geothermal energy potential of 29 GWe spread throughout Indonesia. Geothermal sources that have low steam quality can be used to generate electricity with the Organic Rankin Cycle (SRO). SRO uses organic fluids which have a low boiling point so they can be used as a heat source. Utilization of SRO as Waste Heat Recovery is an increase in the use of renewable energy in Indonesia. In reducing the performance load of the cycle, the recuperator can be added as a supporting component to the Organic Rankin Cycle. By designing a recuperator the load of heating and cooling components will be lighter so that the efficiency value of the cycle will increase. The aim of this research is to design a recuperator in organic rankin cycle (SRO) by analyzing the cycle using organic fluids R123, n-pentane, and n-butane and to calculate the economic feasibility of designing a recuperator in SRO. This study used a brine temperature of 169.932 oC from a PLTP which produced the highest efficiency in an organic rankine cycle of 14.40% with n-pentane organic working fluid. The recuperator design uses n-pentane working fluid which produces a heat transfer effectiveness value of 23.76%. Heat transfer in the recuperator is influenced by the large cross-sectional area which includes the length of the pipe and the number of pipes designed. The results of the economic feasibility calculations in this study are the NPV > 0 and the long time to return on investment using the payback period (PP) method for 4.83 years. Keywords: Organic Rankine Cycle (SRO), Recuperator, PLTP, brine